Problematika Guru Dalam Menerapkan Kurikulum Merdeka Belajar Di Sekolah Dasar Swasta Jakarta - Sri Nurafifah; Ajeng Tina Mulyana; Saat Safaat; Akhmad Subkhi Ramdani (Jurnal Lensa Pendas, 2025)
This study aims to determine the implementation of the independent learning curriculum, the problems of teachers in implementing the independent learning curriculum and how teachers overcome the problems of implementing the independent learning curriculum at SD Tirtamarta- BPK Penabur. This study uses a qualitative approach with a descriptive research type. The subjects of this study were the School, teachers and students of SD Tirtamarta- BPK Penabur. Data collection was carried out through observation, interviews and documentation. The data analysis techniques used were power reduction, data presentation and drawing conclusions. Based on the results of the study, it was concluded that the implementation of the independent curriculum had been implemented at SD Tirtamarta- BPK Penabur with project-based learning activities, diagnostic, formative and summative assessments and subject-based learning, science, report cards, ATP and teaching modules worked on in groups. The problems experienced by teachers in implementing the independent learning curriculum in planning, implementing and assessing learning were the difficulty of analyzing CP, formulating TP and compiling ATP and teaching modules, determining learning methods and strategies and lack of time allocation for project-based learning.